Hope and trust in times of Zika: the views of caregivers and healthcare workers at the forefront of the epidemic in Brazil. Issue 8 (18th July 2020) - Simas, Clarissa; Penn-Kekana, Loveday; Kuper, Hannah; Lyra, Tereza Maciel; Moreira, Maria Elisabeth Lopes; de Albuquerque, Maria do Socorro Veloso; de Araújo, Thália Velho Barreto; de Melo, Ana Paula Lopes; Figueira Mendes, Corina Helena; Nunes Moreira, Martha Cristina; Ferreira do Nascimento, Marcos Antonio; Pimentel, Camila; et al.
Abstract: This article investigates how hope and trust played out for two groups at the forefront of the Zika epidemic: caregivers of children with congenital Zika syndrome and healthcare workers. We conducted 76 in-depth interviews with members of both groups to examine hope and trust in clinical settings, as well as trust in public institutions, in the health system and in the government of Brazil. During and after the Zika epidemic, hope and trust were important to manage uncertainty and risk, given the lack of scientific evidence about the neurological consequences of Zika virus infection. The capacity of healthcare workers and caregivers to trust and to co-create hope seems to have allowed relationships to develop that cushioned social impacts, reinforced adherence to therapeutics and enabled information flow. Hope facilitated parents to trust healthcare workers and interventions. Hope and trust appeared to be central in the establishment of support networks for caregivers. At the same time, mistrust in the government and state institutions may have allowed rumours and alternative explanations about Zika to spread. It may also have strengthened activism in mother's associations, which seemed to have both positive and negative implications for healthcare service delivery. The findings also point to distrust in international health actors and global health agenda, which can impact community engagement in future outbreak responses in Brazil and other countries in Latin America.